1993
DOI: 10.1182/blood.v81.3.835.835
|View full text |Cite
|
Sign up to set email alerts
|

Determination of human platelet antigen frequencies in the Dutch population by immunophenotyping and DNA (allele-specific restriction enzyme) analysis

Abstract: Platelets from 200 random Dutch blood donors were typed for the human platelet alloantigens HPA-1 to -5 recognized at present and for Naka. Naka is an epitope on glycoprotein IV, not expressed on the platelet of individuals with hereditary GP IV deficiency. Platelet immunofluorescence and monoclonal antibody-specific immobilization of platelet antigens (MAIPA) were applied for this purpose. The observed phenotype frequencies were 97.86% and 28.64% for HPA-1a and -1b, 100% and 13.15% for HPA-2a and -2b, 80.95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
93
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(106 citation statements)
references
References 0 publications
11
93
2
Order By: Relevance
“…In addition, the difference in allelic distribution in Italian and other populations could be another possible explanation for the conflicting results. However, the frequency of the Pl A genotypes in our control group is similar to those found in a north European population-based study [13] and to those of the control group of other studies on Pl A1 /Pl A2 polymorphism [6][7][8][9][10].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, the difference in allelic distribution in Italian and other populations could be another possible explanation for the conflicting results. However, the frequency of the Pl A genotypes in our control group is similar to those found in a north European population-based study [13] and to those of the control group of other studies on Pl A1 /Pl A2 polymorphism [6][7][8][9][10].…”
Section: Discussionsupporting
confidence: 89%
“…Genomic DNA was amplified by polymerase chain reaction (PCR) using primers flanking the part of the genomic DNA that contains the C→T substitution at position 1565 in exon 2 of the glycoprotein IIIa gene; the C→T substitution creates a MspI restriction enzyme cleavage site that allows the Pl A1 allele to be distinguished from the Pl A2 allele [13]. The PCR products were digested with MspI (MspI, MBI Fermentas, Lithuania), generating two fragments of 279 bp and 197 bp in the presence of the Pl A1 allele, whereas three fragments of 197 bp, 173 bp, and 106 bp were observed when the Pl A2 allele was present.…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…To further substantiate the alloreaction, patients with platelet-specific antibodies were genotyped for HPA-1 to -5. Genomic DNA was isolated by the salting-out procedure from whole blood anticoagulated with K-EDTA and used for genotyping for HPA-1, -2, -3 and -5, as described previously (Simsek et al, 1993;Holensteiner et al, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Recent population studies have shown that phenotype and genotype frequencies of some platelet antigens vary considerably among different ethnic groups. These frequencies in Caucasians of North America and Europe (Mueller-Eckhardt et al, 1990;Kiefel et al, 1993;Simsek et al, 1993;MunÄ iz-Diaz et al, 1998) differ from those in non-Caucasian populations (Shibata et al, 1986;Saji et al, 1989;Santoso et al, 1993). Nevertheless, data on populations in North Africa and Negroid populations are scant.…”
mentioning
confidence: 99%